Hydrogeochemistry of Water Sources in Obimo and its Environs, Nsukka LGA, Enugu State, Southeastern Nigeria - Okonkwo, Austin C.; Iyi, Emmanuel C.; Nwatarali, Nnaeto R. A.; Ike, Ozoemena C.; Nsude, Okechukwu P.; Eze, Onyinye L.; Aganigbo, Chigozie I.; Ezike, Ejiofor C.; Amoke, Aniebonam I.; Utazi, Benjamin A. (European Journal of Applied Sciences, 2026)
The hydrochemistry of water sources in Obimo and its environs has been carried out. The study area lies within latitudes 060 46I 00IIN and 060 50I 00IIN and longitudes 0070 18I 00IIE and 0070 22I 00IIE, with an area extent of 54.76Sqkm. It is underlain by the Ajalli Formation and Nsukka Formation. A total of five (5) water sources were sampled. Four (4) springs sources and one (1) hand dug well source. The spring sources are Adagboro, Omorimo, Ukpata and Ugolo. The physical parameters were tested insitu using integrated geochemical equipment while the chemical parameters was analyzed in the laboratory using Atomic Adsorption Spectrophotometer (AAS). The average values of temperature, pH and electrical conductivity are 25.2 oC, 8.91 and 73.0µS/cm respectively. The pH value implies slightly alkaline water. Color, taste and odour are less significant in observation. The average elemental ion concentration for the cations and anions analyzed are in the following order: Ca2+ > K+ > Na+ > Mg2+ and > CL- > > > respectively. The elemental ion concentration for all cations and anions are far below the WHO drinking water standard. Hence, Obimo water sources are safe for drinking water with respect to the cations and anions. Fe2+ average concentration is 1.63mg/l which largely exceeds the WHO drinking water standard. Possible source is geogenic. TH of Obimo water sources are classified as moderately hard to hard water. The average TDS is 49.1mg/l. this very low TDS implies low concentration of dissolved mineral and salts in Obimo water sources. ORP varies from -174mV to 156mV with an average of -44.4mV. A reducing environment is suggested. SAR classified the water sources as excellent for irrigation purposes. MAR also classified the Obimo water sources as low magnesium, implying calcium – type water. Analysis of Piper trilinear diagram classified the natural water sources as Ca2+ Mg2+ type. The study has shown the water sources in Obimo suitable has shown the water sources in Obimo suitable for as drinking water and other purposes.